Correlation between the Achievement of Reading Skill and Writing Skill of English Study Program Students - Budi, Agus Setia (Journal of English in Academic and Professional Communication, 2020)
This study was conducted to find out whether or not there was a correlation between learning achievement of reading skill and writing skill. This study was a comparative study to determine the relationship between variables that cannot be done experimentally because the independent variables had worked and had an influence on the dependent variable (effect). The subjects of this study were all students of the English Study Program for Semester 1 and 2 Academic Year 2018/2019. They were 80 students who have taken reading courses (Literal Reading and Interpretive Reading) and writing courses (Paragraph Writing and Essay Writing). The data collection method used in this study were observation and documentation. The data obtained was analyzed by using Correlation Test and Significance Test. The result of this study showed that reading skill had a positive relationship with writing skill. The Correlation Coefficient (r) or r-count of the reading skill and writing skill was 0.897. It can be concluded that there was a positive relationship between the students’ reading skill and writing skill.